Lipid accumulation inhibitory activities of novel isoxazole-based chenodeoxycholic acids: Design, synthesis and preliminary mechanism study. Issue 17 (15th September 2018) - Qiu, Rongmao; Luo, Guoshun; Li, Xinyu; Zheng, Fan; Li, Haolin; Zhang, Jin; You, Qidong; Xiang, Hua
Graphical abstract: Highlights: A series of isoxazole-chenodeoxycholic acid hybrids have been designed and synthesized. The most active compound 16b reduced the lipid accumulation up to 30.5%. 16b blocked lipid accumulation via activating FXR-SHP-SREBP-1c signaling pathway. 16b fitted well in the binding pocket of FXR and displayed satisfied physical property. Abstract: In continuation of our drug discovery program on hyperlipidemia, a series of novel isoxazole-chenodeoxycholic acid hybrids were designed, synthesized and evaluated for their lipid-lowering effects. Preliminary screening of all the synthesized compounds was done by using a 3T3-L1 adipocyte model, in which the most active compound 16b could significantly reduce the lipid accumulation up to 30.5% at a nontoxic concentration 10 μM. Further mechanism studies revealed that 16b blocked lipid accumulation via activating FXR-SHP signaling pathway, efficiently down-regulated the expression of key lipogenesis regulator SREBP-1c.